Fermentation of faba bean flour as a pre-treatment in high-moisture extrusion for simultaneous fortification of vitamin B12 and reduction of raffinose oligosaccharides in meat analogues - Katja Kantanen; Bhawani Chamlagain; Valentina Succi; Siri Seppänen; Minnamari Edelmann; Aino Siitonen; Lotta Kemppinen; Asmo Kemppinen; Mikko Kangas; Pekka Varmanen; Vieno Piironen; Kirsi Jouppila (Future Foods)
Faba bean is a promising ingredient for the production of meat analogues using high-moisture extrusion; however, the presence of antinutrients poses a challenge to its use. Moreover, the deficiency of vitamin B12 in plant-based meat analogues underscores the need to enhance their nutritional profile. This study aimed to fortify faba bean flour with vitamin B12 through fermentation with Propionibacterium freudenreichii and Levilactobacillus brevis while concurrently reducing the content of raffinose family oligosaccharides. The fermentation conditions were initially optimised to maximise active vitamin B12 production, ensure adequate raffinose family oligosaccharide degradation, and maintain microbiological safety. The fermentation was then scaled up to 10 kg and 25 kg. The fermented mass was incorporated into high-moisture extrusion using a wet feeding system, along with a mixture of pea protein isolate and oat fibre concentrate to aid texturization. The extrudates containing the fermented mass exhibited a vitamin B12 content of 75–85 ng/g dry matter, with raffinose, stachyose, and verbascose contents reduced by 53, 56, and 86 %, respectively. Extrudates containing the fermented mass had a layered structure and, compared to control extrudates, a softer texture in general, a more brittle structure, lighter colour, and reduced water absorption capacity.